Rising Trends of Endoscopic Barrett’s Esophagus and Gastric Fundic Gland Polyps in Young Japanese Adults - Atushi Morita,; Akira Horiuchi,; Hiroyoshi Ota,; Ichitaro Horiuchi,; Hidetosi Takada, (Turkish Journal of Gastroenterology, 2023)
Background/Aims: This study examined changes in the esophageal–gastric junction and gastric mucosa in young Japanese adults undergoing endoscopy in the last 15 years.Materials and Methods: This was a retrospective study of young Japanese adults (aged 19-30 years) who underwent esophagogastrod uodenoscopy between 2006 and 2020. The indications were upper gastrointestinal symptoms and anemia. Changes in the appearance of the esophago–gastric junction (i.e., the Z line and distal esophagitis) and gastric mucosa were examined. Endoscopic Barrett’s esophagus was defined using the Japanese criteria.Results: One thousand eight hundred forty-five patients were examined: 848 from 2006 to 2012 [400 males, mean age 26.5 years (range 19-30)] and 997 from 2013 to 2020 [433 males, mean age 26.2 years (range 19-30)]. The proportion showing endoscopic Barrett’s esophagus and gastric fundic gland polyps increased significantly between the 2 periods (12.5% vs. 22.4%, P < .001; 3.4% vs. 7.2%, P < .001) with a significant correlation between the prevalence trends for endoscopic Barrett’s esophagus and gastric fundic gland polyps (r = 0.789, P = .0008). Pathological examination showed that the prevalence of traditional fundic gland polyps unrelated to the use of proton pump inhibitors significantly increased from 40% (4/10) to 81% (25/31) between the 2 periods (P = .04).Conclusion: The prevalence of both endoscopic Barrett’s esophagus and gastric fundic gland polyps among young Japanese adults significantly increased in the last 15 years. The trend in endoscopic Barrett’s esophagus was significantly correlated with that of nonproton pump inhibitor-related gastric fundic gland polyps.Cite this article as: Morita A, Horiuchi A, Ota H, Horiuchi I, Takada H. Rising trends of endoscopic Barrett’s esophagus and gastric fundic gland polyps in young Japanese adults. Turk J Gastroenterol. 2023;34(9):925-931.